Analysis of Curriculum Development and Learning Models of Islamic Religious Education in Non-formal Vocational Education Institutions at LKP El Rahma Education Center - Wendy Asswan Cahyadi; Endin Mujahidin; Didin Hafidhuddin; Siti Qomariyah (Budapest International Research and Critics University, 2022)
Islamic Religious Education (PAI) is often considered as an unimportant subject in shaping students' skills. Islamic religious education is not given the proper portion, even though the ages of vocational education students are those who are able to think. The purpose of this study is to analyze the implementation of curriculum development and PAI learning models. This study uses a quantitative approach. Data collection techniques in this study are experiments and questionnaires. The research was conducted at the El Rahma Education Center Course & Training Institute, Bogor City. Based on the results of the study, the curriculum and learning model of PAI developed were an increase in Islamic religious knowledge in students as evidenced by an increase in grades before and after learning for three semesters. Besides, students are able to achieve PAI learning objectives.